Recurrence of Chronic Myeloid Leukemia during Pregnancy Subsequently Achieving Complete Medical Remission - Sasha Mikhael; Ashlee Pascoe; Joseph Prezzato (Case Reports in Oncological Medicine)
The treatment of chronic myeloid leukemia (CML) with tyrosine kinase inhibitors (TKIs) in reproductive-aged women poses major dilemmas concerning its associated teratogenicity as observed in many animal studies. Much controversy exists regarding continuation versus discontinuation of its use in pregnancy with some studies suggesting safety of TKIs before and during pregnancy and others reporting toxicity and adverse outcomes. TKIs have become a well-established treatment option for CML, significantly improving prognosis, and yet have been reported to be fetotoxic. We present a case of a 25-year-old woman who achieved successful pregnancy and delivery after withholding treatment, meanwhile relapsing, eventually achieving complete molecular remission after reinitiation of high dose dasatinib.